A 7-year-old Male with Penile Hemangioma: A Case Report - Farrelin, Dellananda Christ; Wibawa, Putu Chandra (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2025)
Introduction. Penile hemangioma is a vascular malformation and it is considered rare, with 1-2% of all hemangiomas occurring. The aim of this report is to provide information and the management of penile hemangioma in rural areas. Case. A boy, 7 years old, weighing 25 kg, came to the general surgery department in Malinau General Hospital with a rough, red to purple lesion on the penis since birth. The parents complained that sometimes the patient's urine stream splits into two during urination. The patient was diagnosed with penile hemangioma and treated with propranolol 1 mg/kg/dose for 6 months and hidrosmin 2% ointment. Conclusion. Management of penile hemangioma depends on the size, location and severity of the hemangioma, as well as the patient’s overall health.